The business communication handbook - Dwyer, Judith (Cengage Learning Australia, 2019)
"The Business Communication Handbook, 11e helps learners to develop competency in a broad range of communication skills essential in the 21st-century workplace, with a special focus on business communication. Closely aligned with the competencies and content of BSB40215 Certificate IV in Business and BSB40515 Certificate IV in Business Administration, the text is divided into five sections: Communication foundations in the digital era ; Communication in the workplace ; Communication with customers ; Communication through documents ; Communication across the organisation. Highlighting communication as a core employability skill, the text offers a contextual learning experience by unpacking abstract communication principles into authentic examples and concrete applications, and empowers students to apply communication skills in real workplace settings. Written holistically to help learners develop authentic communication-related competencies from the BSB Training Package, the text engages students with its visually appealing layout and full-colour design, student-friendly writing style, and range of activities."--Publisher website.